2022
DOI: 10.1186/s12934-022-01922-1
|View full text |Cite
|
Sign up to set email alerts
|

Exploring optimal Taxol® CYP725A4 activity in Saccharomyces cerevisiae

Abstract: Background CYP725A4 catalyses the conversion of the first Taxol® precursor, taxadiene, to taxadiene-5α-ol (T5α-ol) and a range of other mono- and di-hydroxylated side products (oxygenated taxanes). Initially known to undergo a radical rebound mechanism, the recent studies have revealed that an intermediate epoxide mediates the formation of the main characterised products of the enzyme, being T5α-ol, 5(12)-oxa-3(11)-cyclotaxane (OCT) and its isomer, 5(11)-oxa-3(11)-cyclotaxane (iso-OCT) as well … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 97 publications
2
27
0
Order By: Relevance
“…However, beyond total taxane recovery, it can be seen that the total oxygenated ratio [oxygenated taxanes (mg/L)/nonoxygenated taxanes (mg/L)] in every single treatment was lower (around 0.9) compared with the results given in treatment 9 which was 1.2 (Figure S10 from the Supporting Information Material and Figure 2b). This result is in agreement with previous studies focusing on the P450 for the synthesis of Taxadiene-5α-ol, highlighting that careful tuning is required to optimize the oxygenated ratio of taxanes Nowrouzi et al, 2022).…”
Section: Resultssupporting
confidence: 92%
“…However, beyond total taxane recovery, it can be seen that the total oxygenated ratio [oxygenated taxanes (mg/L)/nonoxygenated taxanes (mg/L)] in every single treatment was lower (around 0.9) compared with the results given in treatment 9 which was 1.2 (Figure S10 from the Supporting Information Material and Figure 2b). This result is in agreement with previous studies focusing on the P450 for the synthesis of Taxadiene-5α-ol, highlighting that careful tuning is required to optimize the oxygenated ratio of taxanes Nowrouzi et al, 2022).…”
Section: Resultssupporting
confidence: 92%
“…However, beyond total taxane recovery, it can be seen that the oxygenated ratio in every single treatment was lower compared with the results given in treatment 9 (Figure S10 from the supplementary material). This result is in agreement with previous studies focusing on the P450 for the synthesis of Taxadiene-5α-ol, highlighting that careful tuning is required to optimize the oxygenated ratio of taxanes (Nowrouzi et al, 2022; Nowrouzi & Rios-Solis, 2021).…”
Section: Resultssupporting
confidence: 92%
“…Besides this, the limitations of the dodecane overlay method (such as the evaporation of dodecane during cultivation) could make it harder for GC-MS detection. In previous studies using similar yeast strains for the recovery of taxanes and a dodecane overlay method, only 8 (Walls et al, 2021) and 7 (Nowrouzi et al, 2022) taxane compounds were detected in comparison to the 13 taxane compounds found in treatment 9. This highlights the significant benefits of this method for research focusing on the screening and discovery of new natural products.…”
Section: Resultsmentioning
confidence: 88%
“…The drug stabilizes microtubules and in turn blocks cell cycle progression. 12 It was first discovered from the Pacific yew tree ( Taxus brevifolia ) through an anti-cancer screening program conducted by National Cancer Institute (NCI) in 1962. 3 Paclitaxel belongs to a class of diterpenoids from Taxus called taxanes, of which more than 500 structures have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…However, the observed catalytic promiscuity of T5αH on heterologous expression has been a bottleneck in paclitaxel biosynthetic pathway reconstitution for nearly two decades. Expression of T5αH in different heterologous systems, such as Escherichia coli [9][10][11] , Saccharomyces cerevisiae 12,13 and Nicotiana benthamiana 14 ( Supplementary Table 1 ), results in multiple oxidized taxadiene products. While up to 12 products have been reported, 10 only three have been structurally characterized, namely, taxadien-5α-ol ( 2 ), rearranged products 5 (12)-oxa-3 (11)-cyclotaxane (OCT, 3 ) 15 and 5 (11)-oxa-3 (11)-cyclotaxane (iso-OCT, 4 ) 16 .…”
Section: Introductionmentioning
confidence: 99%